Creep in structural-sized beams of argentinean Eucalyptus Grandis - J. C., Piter; C. F., Calvo; A. G., Cuffré; V. C., Rougier; M. A., Sosa Zitto; E.A., Torrán (Maderas. Ciencia y Tecnología, 2014)
The results presented in this paper were obtained from a test carried out during the last series of a research project regarding the creep behaviour of Argentinean Eucalyptus grandis loaded in dry condition. A test with a sample containing 15 structural-sized beams was carried out during 470 days. 7 pieces were free of pith and another 8 contained it. The results allow to compare the creep behaviour of these beams with previous data reported for both structural-sized and small-clear specimens of this timber species and also with those reported for other species. The effectiveness of the criteria adopted by overseas standards as well as those of Latin-American countries for calculating the creep deflections of this timber species under a long-term loading is analysed. The creep deflections obtained in the present research are higher than those calculated by means of the procedures of the Brazilian standard NBR 7190, the European standard Eurocode 5, the American standard National Design Specification for Wood Construction and the Peruvian standard. On the contrary, creep results obtained in this test are lower than those calculated according to the New Zealand standard NZS 3603, the Chilean standard NCh 1198 and the former German standard DIN 1052.